Synthesis and biological evaluation of disulfides bearing 1,2,4-triazole moiety as antiproliferative agents - Xue-Feng Wang; Shuai Zhang; Bao-Lin Li; Ji-Jun Zhao; Yu-Ming Liu; Rui-Lian Zhang; Bo Li; Bao-Quan Chen (Medicinal Chemistry Research, 2017)

The use of toluidine blue staining combined with paraffin sectioning and the optimization of freeze-thaw counting methods for analysing root-knot nematodes in tomato - Xiaoman Li; Wenchao Zhao; Xiaoxuan Zhou; Jiaping Feng; Yingjian Gao; Xuehui Yao; Yang Liu; Jie Liu; Rui Yang; Fukuan Zhao; Shaohui Wang (Horticulture, Environment, and Biotechnology, 2017)

ABA pretreatment enhances the chilling tolerance of a chilling-sensitive rice cultivar - Xiang Hongtao; Wang Tongtong; Zheng Dianfeng; Wang Lizhi; Feng Yanjiang; Luo Yu; Li Rui; Li Zhongjie; Meng Ying; Li Wan; Wang Lianmin; Yang Chunjie (Brazilian Journal of Botany, 2017)

NCAM affects directional lamellipodia formation of BMSCs via β1 integrin signal-mediated cofilin activity - Jia-Jia Bi; Jing Li; Bin-Feng Cheng; Hai-Jie Yang; Qiong-Qiong Ding; Rui-Fei Wang; Su-Juan Chen; Zhi-Wei Feng (Molecular and Cellular Biochemistry, 2017)

Bioorganic fertilizer maintains a more stable soil microbiome than chemical fertilizer for monocropping - Feng Cai; Guan Pang; Rui-Xia Li; Rong Li; Xiao-Long Gu; Qi-Rong Shen; Wei Chen (Biology and Fertility of Soils, 2017)

Association of ACYP2 and TSPYL6 Genetic Polymorphisms with Risk of Ischemic Stroke in Han Chinese Population - Yiqian Liang; Rui Zhang; Shuo Zhang; Guofa Ji; Puyu Shi; Tian Yang; Feng Liu; Jing Feng; Chunqi Li; Dangshe Guo; Mingwei Chen (Molecular Neurobiology, 2017)

Cold-Inducible Protein RBM3 Protects UV Irradiation-Induced Apoptosis in Neuroblastoma Cells by Affecting p38 and JNK Pathways and Bcl2 Family Proteins - Rui-Juan Zhuang; Jian Ma; Xiang Shi; Fei Ju; Shuang-Ping Ma; Lei Wang; Bin-Feng Cheng; Yan-Wen Ma; Mian Wang; Tong Li; Zhi-Wei Feng; Hai-Jie Yang (Journal of Molecular Neuroscience, 2017)

Efficacy and safety of probiotic-supplemented triple therapy for eradication of Helicobacter pylori in children: a systematic review and network meta-analysis - Jue-Rong Feng; Fan Wang; Xiao Qiu; Lynne V. McFarland; Peng-Fei Chen; Rui Zhou; Jing Liu; Qiu Zhao; Jin Li (European Journal of Clinical Pharmacology, 2017)

Behavioral responses of the egg parasitoid Trissolcus japonicus to volatiles from adults of its stink bug host, Halyomorpha halys - Yong-Zhi Zhong; Jin-Ping Zhang; Li-Li Ren; Rui Tang; Hai-Xia Zhan; Guo-Hua Chen; Feng Zhang (Journal of Pest Science, 2017)

Spatiotemporal Variability of Contaminants in Lake Water and Their Risks to Human Health: A Case Study of the Shahu Lake Tourist Area, Northwest China - Peiyue Li; Wei Feng; Chenyang Xue; Rui Tian; Siting Wang (Exposure and Health, 2017)

Oxidative Damage Induced by Arsenic in Mice or Rats: A Systematic Review and Meta-Analysis - Mengchuan Xu; Dongsheng Rui; Yizhong Yan; Shangzhi Xu; Qiang Niu; Gangling Feng; Yan Wang; Shugang Li; Mingxia Jing (Biological Trace Element Research, 2017)

Characterization of a neutral recombinant xylanase from Thermoactinospora rubra YIM 77501T - Yi-Rui Yin; Qing-Wen Hu; Wen-Dong Xian; Feng Zhang; En-Min Zhou; Hong Ming; Min Xiao; Xiao-Yang Zhi; Wen-Jun Li (Antonie van Leeuwenhoek, 2017)

Costimulation of soil glycosidase activity and soil respiration by nitrogen addition - Ji Chen; Yiqi Luo; Jianwei Li; Xuhui Zhou; Junji Cao; Rui‐Wu Wang; Yunqiang Wang; Shelby Shelton; Zhao Jin; Laura M. Walker; Zhaozhong Feng; Shuli Niu; et al. (Global Change Biology, 2017)
Unprecedented levels of nitrogen (N) have been deposited in ecosystems over the past century, which is expected to have cascading effects on microbially mediated soil respiration ( SR ). Extracellular enzymes play critical roles on the degradation of soil organic matter, and measurements of their activities are potentially useful indicators of SR . The links between soil extracellular enzymatic activities ( EEA s) and SR under N addition, however, have not been established. We therefore conducted a meta‐analysis from 62 publications to synthesize the responses of soil EEA s and SR to elevated N. Nitrogen addition significantly increased glycosidase activity ( GA ) by 13.0%, α ‐1,4‐glucosidase ( AG ) by 19.6%, β ‐1,4‐glucosidase ( BG ) by 11.1%, β ‐1,4‐xylosidase ( BX ) by 21.9% and β ‐D‐cellobiosidase ( CBH ) by 12.6%. Increases in GA were more evident for long duration, high rate, organic and mixed N addition (combination of organic and inorganic N addition), as well as for studies from farmland. The response ratios ( RR s) of GA were positively correlated with the SR ‐ RR s, even when evaluated individually for AG , BG , BX and CBH . This positive correlation between GA ‐ RR and SR ‐ RR was maintained for most types of vegetation and soil as well as for different methods of N addition. Our results provide the first evidence that GA is linked to SR under N addition over a range of ecosystems and highlight the need for further studies on the response of other soil EEA s to various global change factors and their implications for ecosystem functions.

Nurr1 promotes intestinal regeneration after ischemia/reperfusion injury by inhibiting the expression of p21 (Waf1/Cip1) - Guo Zu; Jihong Yao; Anlong Ji; Shili Ning; Fuwen Luo; Zhenlu Li; Dongcheng Feng; Yiqi Rui; Yang Li; Guangzhi Wang; Xiaofeng Tian (Journal of Molecular Medicine, 2017)